Using GST as A Tool for Public Awareness Promoting Sustainable Consumer Behavior Through Tax Policy - Karmani, Santosh Tirathdas; Acharekar, Sachin Vilas; Pruswani, Khushbu Jetho; Mirwani, Poonam Motumal; Raut, Tushar Balkrishna (International Journal of Accounting and Economics Studies, 2025)
Sustainability is a growing concern at the global level, and governments are using various tax policies, such as the Goods and Services Tax (GST), to persuade consumers to adopt sustainable habits. The purpose of this study is to examine the impact of GST on public awareness and consumer behaviour to create sustainable consumption patterns. The survey was conducted with 100 respondents from the four cities of Maharashtra, India, using descriptive and chi-square tests to examine whether GST awareness affects sustainable behaviour. A recent study showed that most people know what GST is and consider it a system to be used as an instrument of sustainability. More than half of the respondents reported that GST was a reason for purchasing environmentally friendly products.  However, this remains challenging because of inadequate information, confusing tax rates, and a low awareness of green alternatives. The study employed basic statistical techniques to assess the effect of GST on not only awareness but also behavior, and worthwhile results were obtained from both. These results indicate that GST has the prospective to be an effective instrument for promoting sustainable development, especially when it is complemented by enhanced public education and more progressive tax regulation. These findings indicate that green consumption can be promoted through government policies, including public awareness campaigns. Businesses might also be able to use incentives connected to GST to encourage such ‘green’ products.
Keywords: Consumer Behavior, Goods and Services Tax Policy, Green Product, Sustainable, Public awareness